2007
DOI: 10.1002/joc.1598
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity study of the urban heat island intensity to urban characteristics

Abstract: A detailed urban surface exchange parameterization, implemented in a meso-scale atmospheric model, has been used to study the urban heat island (UHI) intensity during a summer period in the city of Basel, Switzerland. In this urban parameterization, the city is represented as a combination of three urban classes (road, roof and wall), characterized by the size of the street canyon and the building and is thus able to take into account the momentum sink over the entire height of the building, as well as the sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 34 publications
6
55
0
4
Order By: Relevance
“…The average UHI approaches zero degrees close to sunrise (between 05:00 and 06:00 h LT) and reaches the largest negative values at about 08:00 h LT. In the morning and afternoon, the average UHI gradually increases and reaches a maximum at about 18:00 h LT. A stronger UHI in the night-time hours was also found in previous studies (Hamdi & Schayes 2008. These studies suggested that the UHI disappearing after sunrise in the morning is due to the effective heat storage, shadowing and low solar radiation, which make urban areas warm up slower than rural areas.…”
Section: Uhi Intensitiessupporting
confidence: 78%
“…The average UHI approaches zero degrees close to sunrise (between 05:00 and 06:00 h LT) and reaches the largest negative values at about 08:00 h LT. In the morning and afternoon, the average UHI gradually increases and reaches a maximum at about 18:00 h LT. A stronger UHI in the night-time hours was also found in previous studies (Hamdi & Schayes 2008. These studies suggested that the UHI disappearing after sunrise in the morning is due to the effective heat storage, shadowing and low solar radiation, which make urban areas warm up slower than rural areas.…”
Section: Uhi Intensitiessupporting
confidence: 78%
“…Unfortunately, natural cooling processes of evaporation and transpiration are often much reduced in part due to vegetation replacement with impervious surfaces. Recent studies showed that urban locations with a greater percentage of vegetated area are frequently cooler, as is a city with an overall greater percentage of vegetative cover density [2,18,19]. The magnitude of the heating effect in an urban heat island is also dependent upon the georgraphical location of the city.…”
Section: Alterations To Climate Variablesmentioning
confidence: 99%
“…Numerous concepts have been developed to mitigate the heat load in urban areas, such as customizing urban vegetation for shading and evaporative cooling (Spronken-Smith and Oke 1998; Solecki et al 2005;Gill et al 2007;Memon et al 2008;Bowler et al 2010;Oliveira et al 2011;Fallmann et al 2014), introducing open water surfaces (Hathway and Sharples 2012;Theeuwes et al 2013), planning of built structures that support ventilation by choosing an appropriate geometry and size of buildings and street areas (Ali-Toudert and Mayer 2007a, b;Middel et al 2014), and applying suitable materials and colours for buildings to reduce the heat storage and the absorption of solar radiation (Hamdi and Schayes 2008;Krayenhoff and Voogt 2010;Santamouris et al 2012). Increase in vegetation and water surfaces, known as green and blue infrastructure, is of particular interest due to their multiple functionality and benefits for the urban environment, such as increasing urban biodiversity and improving air quality in case of urban vegetation (Akbari et al 2001).…”
Section: Introductionmentioning
confidence: 99%